Double-sided linear induction motor with a rotary solid steel-secondary disc - Kurum, H.; Shobair, A.I.A. (My University, 2000)
The performance of a double-sided linear induction motor (DLIM) with a rotary steel-secondary disc is investigated. The thrust force found experimentally is compared with the theoretical thrust force found by the first author earlier using a two dimensional field analysis [8]. In this analysis, periodic variation with time and periodic distribution with distance is assumed. The normal j-operator method of representing steady-state a. c. quantities is adopted. The travelling wave is assumed to move tangentially along the stator length. Using Maxwell's equations, expressions for the thrust, force and the disc current density were obtained.
Keywords: Disc current density; Disc rotor; Double-sided stator; Linear induction machine; Magnetic field strength; Thrust force